ANALISIS KELAYAKAN BUDIDAYA IKAN NILA (Oreochromis niloticus) DALAM KERAMBA JARING APUNG DI DESA SILALAHI III KECAMATAN SILAHISABUNGAN KABUPATEN DAIRI PROVINSI SUMATERA UTARA - Sudiarno Tamba; M. Ramli; Hendrik ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on 3rd until 10th January 2013. This study aims todetermine how much of the investment and operational costs , feasibility andproblems faced by fish farmers in the cultivation of tilapia (Oreochromis niloticus) infloating net cages in Silalahi III village. The method used in this research is astratified random sampling method with respondents are 8 farmers were divided into3 categories.The results of this research indicate that business investment tilapia farming infloating cages for cultivation category I is Rp.82.743.750,-/unit cultivation withoperational costs Rp.66.846.917,-/period, for category II the investments be requiredRp.167 928 125,-/unit cultivation with operational costs Rp.130.933.792,-/period andinvestments for the cultivation of category III is Rp.397.521.250,-/unit cultivationwith operational cost Rp.317.654.250,-/period. The value BCR of tilapia fish farmersin the village Silalahi III is between 1.1968 until 1.234, value of FRR is 31.79% until37.41% and the value of PPC 5.35 period until 6.29 to period. Based on the analysisof the research, we conclude that the business is financially profitable and feasible tobe developed. The cultivation are most feasible to be developed based on the resultsof the analysis of feasible is a cultivation that occupied by farmers category III withBCR value is 1,2340, FRR 37.41%/year and PPC is 2 years and 8 months. Theproblems faced by farmers in the cultivation is a mortality of seeds cause the seed cannot adapt to the environment and the farmers have not been able to deal with adisease that occurs in fish.Keyword: Silalahi III village, investment, BCR, FRR, PPC, Oreochromis niloticus